High diversity and early radiation of organic-walled phytoplankton in southern Baltica during the Middle-Late Ordovician – evidence from the Borenshult-1 drillcore of southern Sweden - Rubinstein, Claudia Viviana (2023)
Highly diverse and well preserved organic-walled phytoplankton were recorded from the Darriwilian–early Katian interval of the Borenshul-1 drillcore. We identified 154 species in 53 genera and three assemblages were distinguished; Assemblage A of a late Darriwilian age, Assemblage B of a Sandbian age (further subdivided into sub-assemblages B1 and B2), and Assemblage C dated as Katian. Taxa with ‘Silurian affinities’ with previous first appearance datum in the early Silurian, Hirnantian, such as Metaleiofusa and Visbysphaera are here recorded from the late Darriwilian and Sandbian respectively. These occurrences question the relationship between the appearance of pioneering phytoplankton morphotypes and the Hirnantian glaciation. Other taxa with no pre-Silurian records such as Visbysphaera pirifera subsp. minor, Petaloferidium cazurrum and Dorsennidium cf. D. estrellitae are here present in the Sandbian, where bentonite beds are intercalated. The diversity curve of acritarchs shows similarities with those proposed for the Darriwilian-Katian of Baltica with main differences in the interval with bentonite beds representing an intense volcanic activity. The species Metaleiofusa arcuata Wall is here emended and a new combination is proposed Petaloferidium cazurrum (Cramer) comb. nov. The genus Fankea is recorded for the first time from Swedish strata, suggesting a dominant high to middle latitudinal distribution instead of a Perigondwanan distribution. We contend that the location of paleo-southern Sweden contributed to the great diversity seen, since a middle-low latitude provided a suitable habitat with warm, shallow water, rich in nutrients.